Experimental Investigation on Self-Compacting Fiber Reinforced Concrete Slabs - Zarrinkafsh, Orod (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
ABSTRACT: The purpose of this thesis is to determine the effect of steel fibers on mechanical performance of traditionally reinforced self-competing concrete (SCC) slabs. The design is based on flexural failure; subsequently the dimensions of slabs are determined to prevent shear failure. In this study, slabs designed for concrete classes of C20 and C40 with self-compacting concrete in the dimensions of 2200×300×200 mm were tested. For each type of mix, four different volume percentages of 60/30 (length/diameter) fiber (0.0%, 1.0%, 1.5% and 2%) were used and it provided a total of 14 types of slab models. For these tests, an IPE 400 was used by two shafts beneath it for dividing the load in two equal parts. Data Logger machine was used to crack the slabs by applying the two point load in the middle of the slab. During the test, 4 strain sensors were placed at the top and bottom of each slab and also a transducer was placed at the bottom center of it. According to the experimental tests which have been made in this investigation, the result revealed that fibers can improve some properties of self-compacting concrete such as flexural strength and enhance mechanical performance. By performing flexural tests, slabs behavior were improved due to fiber influence on energy absorption and flexural behavior. The results clearly showed that the use of fiber can improve the post-cracking behavior. And also, fiber can increase the tensile strength by bridging through the cracks. Therefore, steel fibers increase the ductility and energy absorption capacity of RC elements subjected to flexure. Keywords: Self-Compacting Concrete, Steel Fibers, Flexural Strength, Reinforced Concrete, Energy Absorption Capacity. ………………………………………………………………………………………………………………………… ÖZ: Bu çalışmanın amacı betona karıştrılan çelik liflerin kendinden yerleşen betonda kullanılması ile üretilen kirişlerin mekanik özelliklerindeki değişikliklerin belirlenmesidir. Kirişlerin ve plakların boyutları ise betonun eğilme dayanımı ve kesme kuvvetleri esas alınarak tasarlanmıştır. Tasarlanan beton sınıfı C20 ve C40 olarak düşünülmüş ve 2200x300x200 mm boyutlarındaki plakalar üretilmiştir. Her bir karışımda 60/30 narinlik oranına sahip tek tip ve dört değişik çelik lif hacmi (%0, %1, %1,5 ve %2) kullanılarak 14 değişik plaka üretilmiştir. Deney düzeneği için IPE400 çelik kiriş ve yükleri iki eşit noktaya dağıtmak amacı ile de iki Çelik silindir kullanıldı. Elde edilen yük, deplasman, birim deformasyonlar data kayıt edici kullanıldı. Deney sırasında, dört adet deformasyon ölçen sensor kullanılarak plakanın üzerinden ve altından very toplanmıştır. Elde edilen sonuçlara balıkdığı zaman ise çelik liflerin kendinden yerleşen beton ile üretilen plakaların eğilme dayanımını ve betonun tokluk enerji emme kapasitesini iyileştirdiği görülmüştür. Bunun dışında yükleme sırasında çatlak oluşumunun da çelik liflerin etkisi ile geciktiği açıkça görülmüştür. Çelik lifler çatlaklar arasında köprü görevi görmekte ve çatlakların ilerlemesi durmaktadır. Anahta Kelimeler: kendinden yerleşen beton, çelik lif, eğilme dayanımı, betonarme betonu, tokluk enerjisi.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2015. Supervisor: Assist. Prof. Dr. Serhan Şensoy.
Keywords: Civil Engineering; Concrete construction; Fiber - reinforced concrete - Self-consolidating concrete; Self-Compacting Concrete, Steel Fibers, Flexural Strength, Reinforced Concrete, Energy Absorption Capacity